Extracorporeal Membrane Oxygenation for Graft Failure after Heart Transplantation: A Multidisciplinary Approach to Maximize Weaning Rate. Issue 9 (September 2014) - Santise, Gianluca; Panarello, Giovanna; Ruperto, Cettina; Turrisi, Marco; Pilato, Gerlando; Giunta, Andrea; Sciacca, Sergio; Pilato, Michele
Objectives: Primary graft failure (PGF) after heart transplantation is a detrimental complication, and carries high morbidity and mortality. The aim of this study was to analyze the results of our multidisciplinary approach in supporting patients affected with PGF after heart transplantation. Methods: Out of 114 consecutive patients receiving orthotopic heart transplantation between January 2006 and July 2013, 18 (15.7%) developed PGF requiring veno-arterial extracorporeal membrane oxygenator (VA-ECMO) support. Fourteen patients were male and the mean age was 49 ± 11 years. General principles in treating the patients were based on a low dose of adrenaline (0.05 mic/kg per min) infusion; femoral intra-aortic balloon pump (13 of the 18 patients); low dose of vasoconstrictors; careful fluid balance; daily echocardiographic transesophageal monitoring. Results: Mean graft recipient pulmonary vascular resistance was 3.6 ± 3.2 WU. Five patients had absolute contraindication to IABP placement. The mean left ventricle ejection fraction pre-VA-ECMO was 18.4% ± 10.2%. The mean VA-ECMO and IABP support times were 6.7 ± 3.2 and 9.2 ± 7.6 days, respectively. Mean VA-ECMO flow was 4164 ± 679 l/min. The mean left ventricle ejection fraction increased to 43.4% ± 17.7% at the end of support. Weaning and discharge rates in patients treated with VA-ECMO+IABP were 84% and 53%, respectively. Causes of death were primarily end-stage organ failure. Conclusions: A multidisciplinary evaluation of ECMO patients done by intensivists, cardiologists, and surgeons may influence weaning and survival rate. Our approach seems to be a safe and reproducible strategy for avoiding left ventricle distension and fluid overload, and for detecting complications that negatively affect outcomes.